Serum α-Tocopherol and γ-Tocopherol Concentrations and Prostate Cancer Risk in the PLCO Screening Trial: A Nested Case-Control Study - Weinstein, Stephanie J.; Peters, Ulrike; Ahn, Jiyoung; Friesen, Marlin D.; Riboli, Elio; Hayes, Richard B.; Albanes, Demetrius (PLOS ONE, 2012)
Background Vitamin E compounds exhibit prostate cancer preventive properties experimentally, but serologic investigations of tocopherols, and randomized controlled trials of supplementation in particular, have been inconsistent. Many studies suggest protective effects among smokers and for aggressive prostate cancer, however. Methods We conducted a nested case-control study of serum α-tocopherol and γ-tocopherol and prostate cancer risk in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial, with 680 prostate cancer cases and 824 frequency-matched controls. Multivariate-adjusted, conditional logistic regression models were used to estimate odds ratios (OR) and 95% confidence intervals (CIs) for tocopherol quintiles. Results Serum α-tocopherol and γ-tocopherol were inversely correlated (r = −0.24, p<0.0001). Higher serum α-tocopherol was associated with significantly lower prostate cancer risk (OR for the highest vs. lowest quintile = 0.63, 95% CI 0.44–0.92, p-trend 0.05). By contrast, risk was non-significantly elevated among men with higher γ-tocopherol concentrations (OR for the highest vs. lowest quintile = 1.35, 95% CI 0.92–1.97, p-trend 0.41). The inverse association between prostate cancer and α-tocopherol was restricted to current and recently former smokers, but was only slightly stronger for aggressive disease. By contrast, the increased risk for higher γ-tocopherol was more pronounced for less aggressive cancers. Conclusions Our findings indicate higher α-tocopherol status is associated with decreased risk of developing prostate cancer, particularly among smokers. Although two recent controlled trials did not substantiate an earlier finding of lower prostate cancer incidence and mortality in response to supplementation with a relatively low dose of α-tocopherol, higher α-tocopherol status may be beneficial with respect to prostate cancer risk among smokers. Determining what stage of prostate cancer development is impacted by vitamin E, the underlying mechanisms, and how smoking modifies the association, is needed for a more complete understanding of the vitamin E-prostate cancer relation.